1999
DOI: 10.1046/j.1471-4159.1999.0720962.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interaction Between Soluble Tubulin and C‐Terminal Domains of N‐Methyl‐D‐Aspartate Receptor Subu

Abstract: Abstract:The cytoplasmic C-terminal domains (CTs) of the NR1 and NR2 subunits of the NMDA receptor have been implicated in its anchoring to the subsynaptic cytoskeleton. Here, we used affinity chromatography with glutathione S-transferase-NR1-CT and -NR2B-CT fusion proteins to identify novel binding partner(s) of these NMDA receptor subunits. Upon incubation with rat brain cytosolic protein fraction, both NR1-CT and NR2B-CT, but not glutathione S-transferase, specifically bound tubulin. The respective fusion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 78 publications
1
16
0
Order By: Relevance
“…␣,␤-Tubulin dimers, cysteine-rich interactor of PDZ three (CRIPT), and MAP2 also seem to lie in the core of the PSD, and these proteins may form complexes with the cDHC dimers. NMDA receptors embedded in the postsynaptic membrane may be associated with the actin filaments via actinin (63), with PSD-95 protein (64), and with ␣,␤-tubulin dimers (65). N-cadherin in the postsynaptic membrane may be associated with the actin filaments of the PSD via ␣-and ␤-catenins, which may in turn bind to the dynein complexes (66).…”
Section: Discussionmentioning
confidence: 99%
“…␣,␤-Tubulin dimers, cysteine-rich interactor of PDZ three (CRIPT), and MAP2 also seem to lie in the core of the PSD, and these proteins may form complexes with the cDHC dimers. NMDA receptors embedded in the postsynaptic membrane may be associated with the actin filaments via actinin (63), with PSD-95 protein (64), and with ␣,␤-tubulin dimers (65). N-cadherin in the postsynaptic membrane may be associated with the actin filaments of the PSD via ␣-and ␤-catenins, which may in turn bind to the dynein complexes (66).…”
Section: Discussionmentioning
confidence: 99%
“…Other proteins such as postsynaptic density-95 (PSD-95) and spectrin bind NR2A (Kornau et al, 1995;Wechsler and Teichberg, 1998), yet we cannot completely rule out the existence of additional factors. Interestingly, tubulin, the monomer of microtubules, binds to NR1 and NR2B, but it has not been tested for its interaction, if any, with NR2A (van Rossum et al, 1999).…”
Section: The Phosphoinositide Modulation Of Ion Channels Includes Nmdarsmentioning
confidence: 99%
“…These findings showed that the DREAM-NR1 interaction was sensitive to Ca 2ϩ . Like many other NR1-interacting proteins, Ca 2ϩ /calmodulindependent protein kinase II (CaMKII) (Leonard et al, 1999), ␣-actinin (Wyszynski et al, 1997), tubulin (van Rossum et al, 1999), and spectrin (Wechsler and Teichberg, 1998) also interact with NR2 subunits. Thus, we could not rule out the possibility of the interaction between DREAM and NR2 subunits.…”
Section: Resultsmentioning
confidence: 99%
“…So far, a number of NR1 or NR2 subunit binding partners have been identified in the postsynaptic density. The NR1 binding proteins include calmodulin (CaM) (Ehlers et al, 1996;Akyol et al, 2004), CaMKII (Leonard et al, 2002), ␣-actinin (Wyszynski et al, 1997;Merrill et al, 2007), tubulin (van Rossum et al, 1999), spectrin (Wechsler and Teichberg, 1998), and neurofilament (Ehlers et al, 1998) and Yotiao (Lin et al, 1998). Here, we identify a new binding partner of the NR1 subunit, DREAM.…”
Section: Discussionmentioning
confidence: 99%